Surgery for recurrent ovarian cancer: Options and limits. (May 2017) - Sehouli, J.; Grabowski, J.P.
Abstract : Cytoreductive surgery is the backbone of the multimodal therapy in primary ovarian cancer patients. Despite the effect of various tumor biological factors such as grading and histological subtype, the surgical outcome is the most important prognostic factor for both progression free- and overall survival. In contrast, the management of recurrent situation has long remained a subject of an emotional international discussion. To date, only few prospective studies have focused on the effect of surgery in relapsed ovarian cancer. The available retrospective data associate complete cytoreduction with prognosis improvement. However, the selection of patients eligible for surgery in recurrent situation is the essential issue. The establishment of predictive factors for complete tumor resection and defining the patient group with recurrent disease who might profit from this approach are crucial. The available predictors of complete resection depend on the results of primary surgery and the current patient's situation. Women who underwent primary complete cytoreduction are in good performance status, and those who have only minimal ascites volume (less than 500 ml) in the recurrent situation have 76% likelihood of undergoing complete resection and survival prolongation. Moreover, the complete cytoreduction in the tertiary cytoreductive approach has been evaluated and showed a potential positive influence on patients' survival. This review concentrates on the recent data and highlights the need of further randomized trials to develop and incorporate operative standards in recurrent ovarian cancer. Highlights: Complete cytoreduction in recurrent ovarian cancer improves the prognosis. Predictive factors of complete cytoreduction are available. Surgery in recurrent ovarian cancer is possible in specialized gyn-oncological centers.